Beyond osteogenesis: an in vitro comparison of the potentials of six bone morphogenetic proteins - Rivera, Jessica C.; Strohbach, Cassandra A.; Wenke, Joseph C.; Rathbone, Christopher R. (Frontiers in Pharmacology, 2013)
Bone morphogenetic proteins (BMPs) other than the clinically available BMP-2 and BMP-7 may be useful for improving fracture healing through both increasing osteogenesis and creating a favorable healing environment by altering cytokine release by endogenous cells. Given the spectrum of potential applications for BMPs, the objective of this study was to evaluate various BMPs under a variety of conditions to provide further insight into their therapeutic capabilities. The alkaline phosphatase activity (ALP) of both C2C12 and human adipose-derived stem cells (hASCs) was measured after exposure of increasing doses of recombinant human BMP-2, -4, -5, -6, -7, or -9 for 3 and 7 days. BMPs -2, -4, -5, -6, -7, and -9 were compared in terms of their ability to affect the release of stromal derived factor-1 (SDF-1), vascular endothelial growth factor (VEGF), and basic fibroblast growth factor (b-FGF) from human bone marrow stromal cells (hBMSCs). Gene expression of ALP, osteocalcin, SDF-1, VEGF, and b-FGF following shRNA-mediated knockdown of BMP-2 and BMP-6 in hBMSCs or human osteoblasts under osteogenic differentiation conditions was also evaluated. Collectively, BMPs-6 and -9 produced the greatest osteogenic differentiation of C2C12 and hASCs as determined by ALP. The hBMSC secretion of SDF-1 was most affected by BMP-5, VEGF by BMP-4, and b-FGF by BMP-2. The knockdown of BMP-2 in BMSCs had no effect on any of the genes measured whereas BMP-6 knockdown in hBMSCs caused a significant increase in VEGF gene expression. BMP-2 and BMP-6 knockdown in human osteoblasts caused significant increases in VEGF gene expression and trends towards decreases in osteocalcin expression. These findings support efforts to study other BMPs as potential bone graft supplements, and to consider combined BMP delivery for promotion of multiple aspects of fracture healing.